Sustainable materials, processes and production - Thompson, Rob (London Thames & Hudson, 2013)
Manufacturing processes--Environmental aspects; Materials--Environmental aspects; Production management--Environmental aspects; Sustainability; Sustainable design
Keywords: Manufacturing processes--Environmental aspects; Production management--Environmental aspects; Materials--Environmental aspects; Sustainability; Sustainable design